Risk-averse and Risk-seeking Investor Preferences for Oil Spot and Futures - Hooi Hooi Lean; Michael McAleer (Tinbergen Institute, 2013)
This paper examines risk-averse and risk-seeking investor preferences for oil spot and futures prices by using the mean-variance (MV) criterion and stochastic dominance (SD) approach. The MV findings cannot distinguish between the preferences of spot and futures markets. However, the SD tests show that spot dominates futures in the downside risk, while futures dominate spot in the upside profit. On the other hand, the SD findings suggest that spot dominates futures in downside risk, while futures dominate spot in upside profit. Risk-averse investors prefer investing in the spot index. Risk seekers are attracted to the futures index to maximize their expected utility but not expected wealth in the entire period, as well as for both the OPEC and Iraq War sub-periods. The SD findings show that there is no arbitrage opportunity between the spot and futures markets, and these markets are not rejected as being efficient.
Keywords: C14; G12; G15; 330; Stochastic dominance; mean-variance; risk averter; risk seeker; futures market; spot market